Isolation and identification of orange M2R and green GS dye degrading bacteria from textile sludge (soil) samples and determination of optimum growth conditions - Alif, Fahim Ahmed (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2016